Evaluasi Tingkat Pelayanan Angkutan Kota Koperasi Wahana Kalpika Provinsi DKI Jakarta terhadap Sistem Transportasi Nasional - Nur Achmad Jabrial (Jurnal Pendidikan Manajemen Transportasi, 2024)
City transportation services, especially in DKI Jakarta Province, refer to the National Transportation System (Sistranas) as stipulated in the Regulation of the Minister of Transportation Number KM. 49 of 2005, which is a systematically organized transportation system to be used as a guideline and basis for planning, developing, and organizing transportation in order to realize effective and efficient transportation services. The Wahana Kalpika Cooperative (KWK) is a small bus (Angkot) public/city transportation business entity whose existence has contributed to public service. KWK has 3,500 members by managing 6,238 fleet units, 1,125 units have joined Mikrotrans Jaklingko, the rest are still regular, providing services on 81 routes throughout DKI Jakarta. The KWK fleet business unit in carrying out its operations requires an evaluation of the level of service provided to be in accordance with (Sistranas). The purpose of this study was to determine the implementation of the KWK service level evaluation whether it has been in accordance with the National Transportation System and its inhibiting factors. The research method uses a descriptive approach with a qualitative approach, which is exploratory. The data analysis technique is subjective by conducting observations or observations that are carried out continuously. For data processing with data categorization, data presentation to conclusions. The implementation of the evaluation of the level of KWK service to Sistranas runs in accordance with the Laws and Regulations, providing maximum service to achieve effectiveness and efficiency for users of its services is measured based on the evaluation carried out by the KWK supervisory team internally and there are external auditors. The results of the evaluation carried out by KWK continue to improve services to the community in providing its service commitments. The inhibiting factor is that in regular services there are fleet units that are no longer allowed to operate, with expired letters, these units are forced to operate on their route but at certain hours and not to the highway to avoid supervision from KWK and the Transportation Agency.